2022
DOI: 10.1016/j.jpha.2021.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral, immunomodulatory, and anticoagulant effects of quercetin and its derivatives: Potential role in prevention and management of COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has caused a devastating health crisis worldwide. In this review, we have discussed that prophylactic phytochemical quercetin supplementation in the form of foods or nutraceuticals may help manage the COVID-19 pandemic. The following evidence supports our argument: first, nuclear factor erythroid-derived 2-like 2 (NRF2) agonists abrogated replication of SARS-CoV-2 in lung cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 70 publications
1
45
0
Order By: Relevance
“…ex DC. Phytomolecules like Vitexin and vitexin analogs ( Rosa et al, 2016 ), Kaempferol and kaempferol analogs ( Lin et al, 2011 ; Swarnalatha et al, 2015 ), Quercetin-3-methyl ether ( Martino et al, 2016 ), Quercetin and quercetin analogs ( Manjunath and Thimmulappa, 2021 ), Acacetin analogs ( Zhao et al, 2014 ), Stigmasterol ( Antwi et al, 2017b ), β-Sitosterol ( Desai et al, 2009 ), Ellagic acid ( Abuelsaad et al, 2013 ), Ferulic acid ( He F. et al, 2021 ), p-Coumaric acid ( Pragasam et al, 2012 ), Chlorogenic acid ( Guo et al, 2021 ), and β-Carotene ( Jyonouchi et al, 2009 ) which were previously been reported from Alternanthera sessilis (L.) R.Br. ex DC., may be responsible for this immunomodulatory potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ex DC. Phytomolecules like Vitexin and vitexin analogs ( Rosa et al, 2016 ), Kaempferol and kaempferol analogs ( Lin et al, 2011 ; Swarnalatha et al, 2015 ), Quercetin-3-methyl ether ( Martino et al, 2016 ), Quercetin and quercetin analogs ( Manjunath and Thimmulappa, 2021 ), Acacetin analogs ( Zhao et al, 2014 ), Stigmasterol ( Antwi et al, 2017b ), β-Sitosterol ( Desai et al, 2009 ), Ellagic acid ( Abuelsaad et al, 2013 ), Ferulic acid ( He F. et al, 2021 ), p-Coumaric acid ( Pragasam et al, 2012 ), Chlorogenic acid ( Guo et al, 2021 ), and β-Carotene ( Jyonouchi et al, 2009 ) which were previously been reported from Alternanthera sessilis (L.) R.Br. ex DC., may be responsible for this immunomodulatory potential.…”
Section: Introductionmentioning
confidence: 99%
“…( Moraes et al, 1994 ). Phytomolecules like Vitexin and vitexin analogs ( Rosa et al, 2016 ), Kaempferol and kaempferol analogs ( Lin et al, 2011 ; Swarnalatha et al, 2015 ), Quercetin and quercetin analogs ( Manjunath and Thimmulappa, 2021 ), Tricin ( Santos et al, 2017 ), Stigmasterol ( Antwi et al, 2017b ), β-Sitosterol ( Desai et al, 2009 ), Ferulic acid ( He F. et al, 2021 ), p-Coumaric acid ( Pragasam et al, 2012 ), and Chlorogenic acid ( Guo et al, 2021 ) which were previously reported from Alternanthera brasiliana (L.) Kuntze, may be responsible towards its immunomodulatory activity. Phytomolecules like Vitexin and vitexin analogs ( Rosa et al, 2016 ), Kaempferol ( Lin et al, 2011 ; Swarnalatha et al, 2015 ), Quercetin-3-methyl ether ( Martino et al, 2016 ), Quercetin and quercetin analogs ( Manjunath and Thimmulappa, 2021 ), Acacetin analogs ( Zhao et al, 2014 ), Stigmasterol ( Antwi et al, 2017b ), and Hydroxytyrosol ( Shan and Miao, 2022 ) which were previously reported from Alternanthera littoralis P.Beauv., may be responsible for its immunomodulatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that it can act as an inhibitor of the ACE2 receptor and prevent the spike glycoprotein:ACE2 complex formation and hence the entry of the virion into host cells [ 48 ]. Quercetin can protect against SARS-CoV-2 infection by impeding virion entry into host cells by modifying spike glycoprotein and/or ACE2, or repressing replication inside the cells by inhibiting 3CL pro [ [49] , [50] , [51] ]. Based on the results of a randomized controlled study presented by Shohan et al [ 52 ], it can be stated that quercetin may be therapeutically effective in reducing the time to clinical improvement in combination with antiviral drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin C, Vitamin E, Curcumin, Selenium [37,106,108,109] Antiviral Selenium, Curcumin, Quercetin, Riboflavin, Vitamin C, Green Tea, Propolis, Resveratrol, Zinc [99,100,103,109,110,111,112,113] Immune response Vitamin A, Vitamin C, Vitamin D, Vitamin B12, Folate, Pyridoxine, Zinc, Nicotinamide, Selenium [38,109,113] Interferon production Vitamin C [111] Virus-ACE2 interaction reduction Quercetin, Curcumin [11]…”
Section: Antioxidantmentioning
confidence: 99%